Crab on a stick: assessing spatial variation in predator community and predation rate using tethered megalopae and underwater video - Ng, Gabriel; Parker, Thomas (Friday Harbor Laboratories, 2014)
Planktonic larval development, common in many benthic marine invertebrates, is associated with both costs and benefits relative to benthic larval development. Costs of being in the plankton include increased susceptibility to advection away from habitat and starvation. Potential benefits include reduction in predation for pelagic larvae. Few studies have measured predation rates on larvae in the field. Even fewer have directly observed larval predation events, documented the specific predator, mode of predation, and intervals between predator attacks. In this study we investigated benthic and pelagic differences in predator assemblage and predation interval on megalopae of the Dungeness crab, Metacarcinus magister. To observe the predation events, we combined methods of tethering larvae with automated motion analysis of underwater camera images from daytime deployments off the dock at Friday Harbor Laboratories, Friday Harbor, WA. We measured number of predation events, the interval in which those events happened, the species of predator, and of other non-predator species that comprised each visible community. Predation was higher on the benthos than the surface, with more total strikes and a shorter interval to predation. Only one predator species was seen during the trials, Artedius harringtoni. These results are consistent with previous studies, and support the novel combination of methods to better inform predation interactions of communities and their relative importance on each species.
Keywords: crab, spatial variation, predator community, predation rate, megalopae